Standardization of procedure for assessing terminal drought stress tolerance induced by foliar spraying of potassium iodide and identification of promising castor germplasm using the developed procedure: TERMINAL DROUGHT STRESS SCREENING IN CASTOR - P LAKSHMAMMA; LAKSHMI PRAYAGA; K ALIVELU; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2019)
Castor cultivated as a rainfed crop in southern India experiences terminal drought stress with cessation of monsoon. Stem reserves act as an important source of carbon for the seeds getting filled when photosynthesis is inhibited by drought and therefore, the ability to mobilize stemreserves towards economic yield is an important trait in selection for terminal drought tolerance. Potassium iodide (KI), a chemical contact canopy desiccant induces leaf desiccation by reducing chlorophyll content and can be used to simulate the conditions of terminal drought stress. This property could be employed for assessing the genotypic variability for stem reserve mobilization trait. During kharif 2015-16, in RG 1826, a genotype that had been identified earlier for root and drought tolerance, KI was sprayed @ 0.2-1.0% at 50% filling of capsules on primary spikes or 1.0-3.0% at 50% filling of capsules on tertiary spikes separately as two sets of foliar sprays. KI spray @1.0% at both the stages recorded total leaf desiccation, less seed yield reduction in primary (16%) and tertiary (29%) order spikes. Hence, 1.0% KI was taken as the optimum concentration to screen castor genotypes for terminal drought stress tolerance. During late rabi 2016-17, 12 germplasm lines with known drought tolerance (moisture stress induced between 30 and 90 DAS) ability and better root growth characters along with two checks were sown and at 100 DAS, KI was sprayed @ 1.0%. Four genotypes, viz., RG82, RG89, RG111, RG1437 with high stem reserve mobilization characterized by <30% reduction in total seed yield and <20% reduction in HI were identified as promising for terminal drought tolerance.